A facile route for the synthesis of mechanically strong MWCNTs/NDs nanobifiller filled polyacrylate composites. Issue 16 (2nd November 2019) - Jabeen, Saira; Gul, Sagheer; Kausar, Ayesha; Muhammad, Bakhtiar; Nawaz, Mohsan; Saud, Khaled M; Farooq, Muhammad
ABSTRACT: We present here the synthesis of novel Nano-Bifiller filled composites with extremely promising material properties. To achieve this goal, initially, poly (methyl methacrylate) (PMMA) and poly (ethylene glycol) (PEG) blend were formed. Later, the matrix was reinforced with purified carbon (P-CNT), amino modified carbon nanotube (PDA-CNT) and amino modified carbon nanotube nanodiamond (PDA-CNT-ND). In this way, three series of nanocomposites, i.e. PMMA/PEG/P-CNT, PMMA/PEG/PDA-CNT, and PMMA/PEG/PDA-CNT-ND were synthesized with varying P-CNT, PDA-CNT and PDA-CNT-ND loading (i.e., 1 wt.%, 3 wt.%, 5 wt.%, 10 wt.%, 30 wt.% and 50 wt.%) by a solution blending route. The reinforcement and loading effect of these three types of nanofillers on the matrix was studied. Studies were performed using Fourier transform infrared spectroscopy (FTIR), mechanical testing, thermogravimetric analysis (TGA), field emission scanning electron microscopy (FE-SEM) and X-ray powder diffraction (XRD) to explore the structural, morphological, mechanical and thermal properties of nanocomposites prepared. The inter-association of poly (methyl methacrylate) and poly (ethylene glycol) (PMMA/PEG) due to hydrogen bonding and covalent attachment of matrix to the sidewalls of nanotubes was confirmed by FTIR spectra. The experimental results showed that a loading of 5 wt. % filler in matrix produced a tensile strength and modulus of 26.4 (MPa) and 1255.75 (MPa) in PMMA/PEG/P-CNT nanocomposites, while 28.8 (MPa) and 1411.04 (MPa) in PMMA/PEG/PDA-CNT nanocomposites and 29.4 (MPa) and 1419.41 (MPa) in PMMA/PEG/PDA-CNT-ND nanocomposites as compared to neat PMMA which has tensile strength and modulus of 21.79 (MPa) and 1083.84 (MPa) respectively. These results depict that bifiller nanocomposites showed better mechanical properties as compared to pristine and amine functionalized MWCNT. Scanning electron microscopy revealed granular morphology with few protruding out carbon nanotubes. Thermal stability of PMMA/PEG/PDA-CNT-ND nanocomposites was found higher than PMMA/PEG/PDA-CNT and PMMA/PEG/P-CNT nanocomposites. The To (369 ° C) and T10 (515 ° C) values for PMMA/PEG/PDA-CNT-ND composites was higher than PMMA/PEG/PDA-CNT [To (354 ° C) and T10 (420 ° C)] and PMMA/PEG/P-CNT composites [To (312 ° C) and T10 (390 ° C)]. These results suggest that the bifiller nanocomposites were thermally more stable. The XRD spectra showed a pronounced XRD peak at 25.9 °, corresponding to (002) reflection of the nanotubes indicating that MWCNT structure was not destroyed during composite formation. The peak appeared at 75.3 ° were indexed to (220) reflections due to nanodiamond structure. GRAPHICAL IMAGE: